Exploration of Experiment Teaching Reform Guided by the Engineering Education Philosophy - Huichun Huang; Guoliang Du; Renjie Hu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In order to make the electronic design contest and reform of experiment teaching to support and promote each other and improve students' practical and innovative ability, the paper analyzed the requirements on the students' ability of comprehensive knowledge application and practice by NUEDC, and the deficiencies of the depth and scope of electronic information professional practice curriculum. Use the issues-based, project-based and case-based engineering education philosophy and teaching methods as orientation. The way of practice teaching reform and the effect of the reform from six aspects are also discussed: the construction of hierarchy practice teaching system, the seminar and the optimizing of teaching content, the engineering teaching method, the experimental teaching environment and full control of network-assisted teaching platform. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3144